2019
DOI: 10.1002/iroh.201801960
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultraviolet radiation on clearance rate of planktonic copepods with different photoprotective strategies

Abstract: We studied two populations of Boeckella gracilipes and two populations of Boeckella gibbosa that inhabit mountain lakes from North-Patagonian Andes with different optical properties. We combined field and laboratory experiments to determine the effects of ultraviolet radiation (UVR) on clearance rate among these taxa that had different UVR defences. The copepod populations differed in photoprotective compounds (carotenoids and mycosporine-like amino acids [MAAs]) and antioxidant enzymes (glutathione S-transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Apart from mortality, UV radiation also affects zooplankton at a sub-lethal level leading to reduced fitness. Recent studies have demonstrated reduced feeding rates in small crustaceans such as copepods, reduced growth in Daphnia and morphological changes in structures used for swimming and feeding in ciliates when exposed to PAR, UV-A and UV-B radiation compared to PAR-only treatments [ 251 , 253 , 255 , 256 ].
Fig.
…”
Section: Aquatic Ecosystemsmentioning
confidence: 99%
“…Apart from mortality, UV radiation also affects zooplankton at a sub-lethal level leading to reduced fitness. Recent studies have demonstrated reduced feeding rates in small crustaceans such as copepods, reduced growth in Daphnia and morphological changes in structures used for swimming and feeding in ciliates when exposed to PAR, UV-A and UV-B radiation compared to PAR-only treatments [ 251 , 253 , 255 , 256 ].
Fig.
…”
Section: Aquatic Ecosystemsmentioning
confidence: 99%
“…Over the past few decades, it has been well demonstrated that nature ultraviolet-B (UV-B) radiation increased signi cantly with the continuing depletion of stratospherico zone, which has becoming one of the grave concerns and most striking global changes [10,11]. There is growing evidence that adverse biological effects of ambient ultraviolet radiation exposure occur in not only marine but also freshwater ecosystem at different trophic levels [11,12], involving algae [13], rotifers [14,15], copepods [16,17], cladocerans [18], shrimps [19,20] and shes [21]. In all cases, UVR was found to harm the organisms in question by damaging DNA directly at the molecular level and affect tness at the individual and population levels [22].…”
mentioning
confidence: 99%
“…UV radiation can also cause sub-lethal effects, such as reduced feeding rates, reduced growth and morphological changes in many organisms [ 247 , 248 ]. These effects have been previously documented in all types of major zooplankton taxa [ 249 251 ], and in recent years include reports on less studied taxa such as ciliates and crab larvae [ 245 , 252 , 253 ].…”
Section: The Adverse Effects Of Uv Radiation and The Defences Against...mentioning
confidence: 99%